Karakteristik Fisiko-Kimia dan Sensori Pempek Ikan Gabus (Channa striata) dengan Penambahan Brokoli (Brassica oleracea) sebagai Pangan Fungsiona - Yulanda Afriani; Susi Lestari; Herpandi Herpandi (Jurnal FishtecH, 2015)
The purpose of this study was to determine the characteristics of the snakehead fish pempek with broccoli addition as a functional food. The design used is a randomized block design with 5-stage treatment that was repeated 3 times. Factors treatment consists of adding broccoli concentrations (0%, 5%, 10%, 15% and 20%). Parameters that observed were physical analysis (elasticity, lightness, chroma and hue), sensory analysis (texture, appearance, color and flavor), proximate analysis, levels of calcium, fiber content and antioxidant activity. Results of research conducted showed that the addition concentration of broccoli into pempek snakehead fish has significant effect (p <0.05) on the physical characteristics and sensory. The average value elasticity ranged from 343.06 to 559.66 gf, lightness 53.1% to 60.20%, chroma 8.36% to 13.23%, and hue 70.23o up 93.8o. Based on the physical parameters (elasticity) and sensory found that treatment A1 (5% addition of broccoli) is the best treatment with 40.89% moisture content, 1.15% ash content, 0.16% fat content, 7.39% protein content, 48.14% carbohydrate content, 2.24% crude fiber content, 106.5 mg/100 g the level of calcium, and 202 ppm antioxidant activity contents